Gene and cell therapies for beta-globinopathies - Malik, Punam; Tisdale, John (Springer New York, 2017)
This book provides a comprehensive review of gene and cell therapy approaches for hemoglobinopathies. It covers the progress and current state of the field in hematopoietic stem cell transplantation for hemoglobinopathies and genetic correction of autologous hematopoietic stem cells. Chapters focus on such topics as the current standards of care and long term outcomes of b-thalassemias and sickle cell disease, the ability to generate autologous embryonic stem cell-like cells from primary somatic cells, and genetic strategies to reactivate fetal hemoglobin production. In addition to offering a thorough review of the field in its present state, this book also sheds light on the major changes expected in coming years. Gene and Cell Therapies for Beta-Globinopathies is part of the American Society of Gene and Cell Therapy sub-series of the highly successful Advances in Experimental Medicine and Biology series. It is essential reading for graduate students, clinicians, and researchers interested in gene and cell therapy.- Resumé vydavatel
Keywords: lékařská genetika; genová terapie; cytologie; kmenové buňky; buněčná terapie; medical genetics; gene therapy; cytology; stem cells; cell therapy; elektronické knihy; sborníky; electronic books; papers of several authors